A Study of Bacterial Disease among the Suspected Cases of Lumbini Provincial Hospital, Butwal, Rupandehi, Nepal - Upadhyay, Maya (Butwal Campus Journal, 2021)
The bacterial disease is a major health problem in Nepal. This study has been done in the Lumbini provincial hospital from January 2021 to June 2021. In a study of bacterial disease among the suspected cases of Lumbini provincial hospital, four types of bacterial diseases were found; TB, pneumonia, leprosy, and meningitis. Among the four diseases, the cases of TB and pneumonia are found higher than that of leprosy and meningitis. The highest cases of TB i.e., 2.5% show in between the age group of 20-30 and 40-50 years of age. The highest cases of pneumonia show in between the age group of 0-10 years i.e., 5.75%. The highest cases of leprosy were found in above 70 years of age group i.e., 2.25% and that of meningitis were found in between the age group of 40-50 years of age i.e., 1%.